Crime and social control in pandemic times - Deflem, Mathieu (Emerald Publishing Limited, 2023)
Theoretically and methodologically diverse, Volume 28 of Sociology of Crime, Law and Deviance addresses important questions of crime, punishment, policing, social control, and law in relation to COVID-19. The pandemic has brought about a wide number of analyses from various viewpoints, but what role has the study of crime, deviance, and social control played? A timely contribution that tackles a variety of related topics and brings together authors from a range of social-science disciplines, Crime and Social Control in Pandemic Times is a diverse and useful resource for those interested in the dynamics of crime and social control at a time of huge global disruption.
Keywords: Crime -- Sociological aspects.; Social control.; COVID-19 Pandemic, 2020- -- Social aspects.; Social Science -- Criminology.; Crime & criminology.; elektronické knihy; electronic books